Patterned crack-free PZT thick films for micro-electromechanical system applications - Dauchy, Florent; Dorey, Robert A. (Springer Science Business Media, 2007)
The fabrication and structuring of multilayer-thick film piezoelectric (PZT-lead zirconate titanate) structures, using composite sol-gel techniques and wet etching is described. The composite sol-gel technique involves producing a PZT powder/sol composite slurry which when spun down, yields films a few micrometres thick. Repeated layering and infiltration has been used to produce PZT films between 10 and 40 μm thick. Due to the low firing temperature (<720°C), it has also been possible to produce PZT films with embedded thin (ca. 100 nm thick) metal electrodes. The PZT thick films have also been structured using a wet etching technique. Examples of features and cavities with lateral dimensions in the order of tens of micrometres are presented. The ability to fabricate and structure thick functional films with embedded metal electrode structures offers the possibility to create novel micro-device structures suitable for use in micro-electromechanical systems (MEMS
Keywords: PZT; MEMS; Patterning